HEDONISME DALAM PELAKSANAAN RITUAL AGAMA HINDU DI BALI - I Made Hartaka; Yunitha Asri Diantary Ni Made (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Religion in today's modern era faces such great challenges.If religion was initially very feared but along with the development of the age humans began to deny the nature of the religion.Modern society is pragmatic thinking, prioritizing a little effort but expecting maximum results, more clearly humans today want everything to be instant.Pleasure and material pleasure become one of the purposes of life. Hedonism that places pleasure as the highest value and must be realized in social practices that in this case are manifested in the implementation of rituals in Hindu communities in Bali.This spiritual hedonism has great peulang in creating hyperitual, where the ritual is carried out beyond the nature of the ritual itself.Religious ritual activities developed into a lifestyle and prestige.In the current era spiritual hedonism is closely related to matrealistic spirituaism, commodity spirituality, market spirituality and money.Considering this understanding prioritizes enjoyment as the highest goal so it requires markets, commodities and money.In essence, the implementation of the ritual will run smoothly and bring peace if based on dharma and during the procession follow the ethics of the religious ritual.Keywords: Hedonism, Rituals, Hinduism